2020
DOI: 10.1177/2516043520957116
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: The dark side and the sunny side for patient safety

Abstract: The COVID-19 crisis has placed an enormous strain on our hospitals and health systems. Caring for the rapidly evolving needs of patients has triggered radical changes in the organization and delivery of services. Some hospitals transformed into huge pulmonary critical care units. Most drastically curtailed the usual elective procedures and preventive care to accommodate the flood of patients requiring intensive care for coronavirus disease. The terrible consequences of the pandemic are obvious, with millions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
7
1
1
Order By: Relevance
“…Indeed, in a recent article published in 2020, a group of diverse researchers agreed that the COVID‐19 pandemic may result in many positive changes in health care, such as upgraded coordination and quality. These changes could be realized through strong commitments to a shared goal, building innovative solutions, and transforming failures into lessons and motivators to achieve future success 18 . Our results are inconsistent with the results of the data from a UK study 12 , which reported a statistically significant reduction in PSIRs after the COVID‐19 crisis.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, in a recent article published in 2020, a group of diverse researchers agreed that the COVID‐19 pandemic may result in many positive changes in health care, such as upgraded coordination and quality. These changes could be realized through strong commitments to a shared goal, building innovative solutions, and transforming failures into lessons and motivators to achieve future success 18 . Our results are inconsistent with the results of the data from a UK study 12 , which reported a statistically significant reduction in PSIRs after the COVID‐19 crisis.…”
Section: Discussioncontrasting
confidence: 99%
“…The pandemic had a few more silver linings for patient safety and health care quality. 7 There has been an increased appetite for data, the more local the better. The Johns Hopkins COVID-19 dashboard achieved celebrity status.…”
mentioning
confidence: 99%
“…My own institution had already begun to wean itself from just-in-time procurement and to improve stockpiling. 7 During the pandemic, it became apparent that this infrastructure was a key component of the COVID-19 response.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We must be discerning with what we read and avoid the cognitive biases introduced by anecdote, sensationalism, and fear. 10 We must enroll our patients in clinical research, trials, and cohort studies whenever possible. We need to collect data and contribute to the collective effort to build a foundation of knowledge and scientific evidence.…”
mentioning
confidence: 99%